1997
DOI: 10.1182/blood.v90.7.2654.2654_2654_2659
|View full text |Cite
|
Sign up to set email alerts
|

The Two Common Mutations Causing Factor XI Deficiency in Jews Stem From Distinct Founders: One of Ancient Middle Eastern Origin and Another of More Recent European Origin

Abstract: Previous studies showed that factor XI (FXI) deficiency commonly observed in Ashkenazi Jews is caused by two similarly frequent mutations, type II (Glu117stop) and type III (Phe283Leu) with allele frequencies of 0.0217 and 0.0254, respectively. In Iraqi Jews, who represent the ancient gene pool of Jews, only the type II mutation was observed with an allele frequency of 0.0167. In this study we sought founder effects for each mutation by examination of four FXI gene polymorphisms enabling haplotype analysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Interestingly, type II mutations could be observed in all Jewish communities and probably appeared in ancient times (586 BC BCÂą Âą70 AD AD) before the divergence of the major segments of this population. On the other hand, type III mutations were solely found in Ashkenazi patients and were supposed to arise more recently [26]. In addition, some correlations have been found between the genotype and FXIc levels or bleeding incidence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, type II mutations could be observed in all Jewish communities and probably appeared in ancient times (586 BC BCÂą Âą70 AD AD) before the divergence of the major segments of this population. On the other hand, type III mutations were solely found in Ashkenazi patients and were supposed to arise more recently [26]. In addition, some correlations have been found between the genotype and FXIc levels or bleeding incidence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Haplotype analysis demonstrated that these two mutations are of ancient origins and arose from distinct founders [12]. Although the type II mutation is also frequent among Iraqi Jews and Palestinian Arabs [12], Phe283Leu is almost unique in Ashkenazi Jews, but it can be rarely observed in other populations [13,14]. A large study performed in the Italian population, besides confirming the Jewish origin of both type II and III mutations, evidenced a significant frequency of the Glu117Stop allele among Italian FXIdeficient patients [13].…”
Section: Introductionmentioning
confidence: 92%
“…by pre-surgical screening or during family studies after identification of homozygous subjects) by which these subjects, usually asymptomatic, were identified. Interestingly, the type III Phe283Leu has been identified in compound heterozygosity in two patients only (allele frequency 3.8%), although the frequencies of the type II and type III mutations (allele frequency 0.00064 and 0.00051 respectively) in an unselected population of 3879 Italian individuals were indeed similar [13], as in Askenazi Jewish [11,12]. However, as most FXI-deficient patients remain asymptomatic, a significant number could go unrecognized, thus causing a diagnostic selection bias and a difficulty in a reliable estimate of the complete genetic background.…”
Section: Genetic Heterogeneity Of Fxi Deficiency In Italymentioning
confidence: 99%
See 1 more Smart Citation
“…Markers used in Jewish or Italian haplotyping in previous studies are shaded in gray(27,28). b Nucleotide number of the intronic polymorphisms have been assigned starting from the nearest splicing junction.…”
mentioning
confidence: 99%